PENGARUH WAKTU PERENDAMAN STEK BATANG VANILI DALAM ZAT PENGATUR TUMBUH ROTOONE – F TERHADAP PERTUMBUHAN VANILI (VANILLA PLANIFOLIA ANDREWS) - Philipus.N. Supardi; Sivester Seda (Agriculture Faculty of Flores University, 2010)
This study aims to determine the effect of immersion time with the vanilla stem cuttings of plan growth regulators Rotoone – F of credit for the growth of roots and shoots of vanilla cuttings. The treatment used in this study is A0 (without immersion), A1 (immersion time 5 min), A2 (soaking time 10 min), and A3 (soaking time 15 min) variable observation in this study is the number of shoots, root number, number of The firs day of growing shoots, shoots length, root length, root diameter, wet weight and dry weight of cuttings of vanilla. The result showed that root growth best to treatment with the immersion time of 15 min (A3) is indicated by the highest number of roots, root length and diameter to treatment with the highest root of soaking time 15 min (A3) in 14 to 28 HST HST. The result showed that the growth of shoots best to treatment with the immersion time of 15 min (A3) is indicated by a number of days the first shoots to grow the fastest, most number of shoots, shoot length, wet weight and dry weight of the highest in treatments with soaking time 15 (A3) in 14 HST to 28 HST.